Islamic values, Doi Menre tradition, Bugis marriage - iling sesukanda (Sinar Lima, 2024)
The researcher was interested in studying strategies for developing the quality of students from the aspect of discipline, foreign language skills (English) and the achievements of students at the Munirul Arifin Islamic boarding school foundation NW Praya. This type of research uses qualitative research with a descriptive approach. The collection methods used are interviews, observation and documentation methods. The results of this research analysis show that there are several strategies implemented by the NW Praya Munirul Arifin Islamic boarding school foundation in developing the quality of students, including: a) discipline aspects, where 1) students are required to behave honestly, 2) providing motivation and advice, 3) establishment of rules; b) aspects of language skills, where 1) Mater of Student program, 2) English camp, 3) Repetition program,; c) aspects of student achievements, where 1) coaching; a) supporting factors, b) inhibiting factors.